Invisible Avant-Garde and Absent Revolution: Walter Benjamin’s New Optics for Moscow Urban Space of the 1920s - Seits, Irina S. (Actual Problems of Theory and History of Art, 2018)
Walter Benjamin spent the fall and winter of 1926-1927 in Moscow. His experience and observations were recorded in “Moscow Diary” and essay “Moscow” (1927). In the present paper, the author refers to the latter text, in which Benjamin reflected on the space of Soviet capital that was undergoing severe transition. Without even mentioning Avant-garde architecture that was being constructed in his presence and that was transforming the living space of the new state on all levels, Benjamin left deep analyses of Moscow’s post-revolutionary urban constitution, revealed its nature, and predicted its future.Walter Benjamin spent the fall and winter of 1926-1927 in Moscow. His experience and observations were recorded in “Moscow Diary” and essay “Moscow” (1927). In the present paper, the author refers to the latter text, in which Benjamin reflected on the space of Soviet capital that was undergoing severe transition. Without even mentioning Avant-garde architecture that was being constructed in his presence and that was transforming the living space of the new state on all levels, Benjamin left deep analyses of Moscow’s post-revolutionary urban constitution, revealed its nature, and predicted its future. Benjamin came to Moscow to observe the Revolution in action, but could not find it. Instead, he saw Constructivism as already dismissed. While recording those huge transformations that he witnessed during his stay, Benjamin had not described them either in terms of new functionalist architecture, or through the reflection on demolition of Empire’s architectural symbols. He turned to other features and spatial dimensions that were not directly related to any particular architecture, such as mobility, rhythm, aura and through which he fully revealed reformation of Moscow space that was initiated by functionalists and supported by the new regime.